Predicting the Quality of Life in Infertile Women Based on Alexithymia and Spiritual health with The Mediating Role of Loneliness - Amini Masouleh, Masumeh; Namvar, Hooman; Aghayousefi, Alireza (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim:Infertility is defined as the absence of pregnancy after one year of adequate and regular intercourse. It is both an individual and social problem that can expose individuals to various psychological and social pressures. The present study was an attempt to predict health-related quality of life in infertile women based on mood and spiritual health and considering the mediating role of feelings of loneliness. Materials and Methods:The study followed a descriptive (non-experimental) method with correlation and structural equations design. Participants were 348 infertile women in the age range of 18-43 years living in Tehran who referred to the infertility clinics and centers in Tehran during 2020. Research tools included standard questionnaires and scales delving into the quality of life, alexithymia, social and emotional loneliness, and spiritual health of the participants of the study. Data analysis was performed using SmartPLS software. Results:The intensity of the effect of alexithymia on health-related quality of life mediated by loneliness was 0.0962 and the intensity of the effect of spiritual health on health-related quality of life mediated by loneliness was 0.1602. Results also showed that the role of loneliness was partial mediation in the sense that mood and spiritual health involved both directly and indirectly, through the feeling of loneliness, in health-related quality of life in infertile women. Conclusion:it can be concluded that alexithymia and spiritual health are the most important predictors of health-related quality of life in women with infertility and the mediating role of loneliness in this relationship signified the importance of this practical concept..